Mental health and suicide literacy among school nurses in Japan: A cross-sectional study - Ayuko Yukawa; Sakurako Kusaka; Satoshi Yamaguchi; Takuya Arai; Fumika Sawamura; Fumiharu Togo; Tsukasa Sasaki (PLoS ONE, 2026)
Background School nurses (SN) are key providers of school health services and play a vital role in promoting adolescent mental health and preventing suicide. However, research into their mental health literacy (MHL) and suicide literacy remains limited. Methods A self-administered questionnaire survey was conducted with 337 SN from Japanese middle and high schools. The survey assessed SNs’ MHL and suicide literacy, including knowledge, attitudes, intended approaches, and confidence in addressing student mental health and suicide risks. Results One-third of SN incorrectly believed that they could manage psychotic symptoms by careful listening alone. Many hesitated to ask students about suicide plans, even when risk was evident. Over half lacked confidence in providing mental health education. Conclusion SNs’ MHL and suicide literacy are currently insufficient in Japan. Developing evidence-based training to improve these competencies is essential to strengthen school health services and promote better adolescent mental health and lower suicide risk.